Enacting effective climate policy advice: institutional strategies to foster saliency, credibility and legitimacy. (30th August 2016) - Bauer, Anja; Pregernig, Michael; Reinecke, Sabine
Abstract : This article asks how scientific advisory institutions (SAIs) in climate policy strive towards effectiveness. Our analysis is grounded on the assumption that effectiveness is not passively experienced but is deliberately enacted by SAIs. We draw on a widely used set of criteria, namely saliency, credibility and legitimacy (SCL). Based on an analysis of 30 SAIs, we map and illustrate the repertoire of strategies and mechanisms that SAIs employ to enhance and demonstrate their saliency, credibility and legitimacy in advice giving. We conclude that SAIs enact SCL on three levels, that is, by means of organisational provisions, procedural setups and rhetorical depictions.